A concerted effort to transfer knowledge within European MNCs. (2015) - Bengoa, Dolores Sanchez; Czinkota, Michael R.; Kaufmann, Hans Ruediger; Schrader, Marc Falko
This conceptual paper contributes to the nascent debate on a stronger appreciation of subsidiaries' contribution to knowledge creation and transfer within the Multinational Corporation (MNC) network reflected by increased levels of reverse and/or horizontal knowledge transfer. Furthermore, the current literature implies scattered evidence with respect to the influential factors and controversial power interests on behalf of the players involved: the MNC headquarter, the individual subsidiaries and between the subsidiaries. For this reason, the paper aims to develop a holistic conceptual framework as a basis for a future research agenda on multidirectional knowledge transfer driven by a concerted effort of all partners involved. Owing to its high cultural density and diversity in a close geographical space, Europe is regarded an ideal and vibrant setting for research on knowledge creation. As a side effect of an increased level of competitiveness, MNCs might play a significant role in contributing to the EU objectives of higher levels of prosperity of an ever more integrated economy and of new energies for the region's technological and industrial development.